2000
DOI: 10.1002/1522-2683(20000801)21:14<3048::aid-elps3048>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel proteins associated with the development of chemoresistance in malignant melanoma using two-dimensional electrophoresis

Abstract: A model system for studying chemoresistance in human melanoma cells (MeWo) has been established utilizing the four commonly used cytotoxic drugs vindesine, cisplatin, fotemustine and etoposide to yield stable drug-resistant sublines. We analyzed phenotypical differences between MeWo cells and their chemoresistant counterparts using two-dimensional electrophoresis. Proteins that were overexpressed in chemoresistant cell lines were purified and identified using matrix assisted laser desorption/ionization-time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 35 publications
1
50
0
2
Order By: Relevance
“…These studies demonstrated the importance of TCTP in maintaining genome stability under genotoxic stress, which is consistent with observations from Fujise's and our own laboratory, showing that TCTP is able to protect cancer cells against the cytotoxicity exerted by DNA-damaging anticancer drugs Bommer et al 2017). The involvement of TCTP in the development of chemoresistance in cancer chemotherapy has also been emphasised by several other papers (Jung et al 2014;Takahashi et al 2010;He et al 2015;Sinha et al 2000). 4.…”
Section: Involvement In Cellular Stress Responsessupporting
confidence: 86%
See 1 more Smart Citation
“…These studies demonstrated the importance of TCTP in maintaining genome stability under genotoxic stress, which is consistent with observations from Fujise's and our own laboratory, showing that TCTP is able to protect cancer cells against the cytotoxicity exerted by DNA-damaging anticancer drugs Bommer et al 2017). The involvement of TCTP in the development of chemoresistance in cancer chemotherapy has also been emphasised by several other papers (Jung et al 2014;Takahashi et al 2010;He et al 2015;Sinha et al 2000). 4.…”
Section: Involvement In Cellular Stress Responsessupporting
confidence: 86%
“…Sinha and co-workers performed a proteomics analysis on human melanoma cell lines that were resistant to drugs like vindesine, cisplatin and etoposide. They identified TCTP as one of four proteins overexpressed in those cell lines, compared to their no-resistant parental cells (Sinha et al 2000). Fujise's laboratory demonstrated TCTP (fortilin)-dependent drug resistance against etoposide (Li et al 2001) and 5-FU in U2OS cells.…”
Section: Mechanistic Involvement In Cancer Progressionmentioning
confidence: 99%
“…Elongation factor-1 delta may have other actions, such as effects on chemotherapy and ionising radiation (Jung et al, 1994;Sinha et al, 2000). Sinha et al (2000) indicated that human EF-1 delta was overexpressed in melanoma cell lines exhibiting chemoresistance towards antineoplastic drugs, such as vindesine, cisplatin, fotemstine and etoposide.…”
Section: Discussionmentioning
confidence: 99%
“…64 By analyzing global protein expression using 2-dimensional gel electrophoresis in drugsensitive and -resistant counterparts in human melanoma cell lines, various proteins have been detected and associated with the drugresistant phenotype. 65 For both approaches, further functional assays are needed to confirm the relevance of the identified molecules in conferring drug resistance in these cells. In light of the evidence gained so far, it appears that the lethality of malignant melanoma is due, to a large extent, to the ability of these tumor cells to resist chemotherapy; and any further knowledge gained on the nature of this resistance would improve the prospects of melanoma therapy.…”
Section: Conclusion and Future Perspectives In Research And Treatmentmentioning
confidence: 99%